Analisis Hukum Bisnis terhadap Risiko UMKM Tanpa Izin di Pusat Oleh-Oleh Bantarjati, Bogor - Andianita Nur Illahiyah Illahiyah; Mohammad Hipni (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
The purpose of this study is to examine the legal and commercial concerns that Micro, Small, and Medium-Sized Enterprises (MSMEs) in Bantarjati Village, Bogor City's souvenir district confront when operating without official company licenses. The study also looks at how these unauthorized enterprises affect consumer protection in the context of company law. This study uses a case study design and a qualitative methodology. In-depth interviews with fifteen MSME players, field observations, and examination of pertinent regulatory papers were used to gather data. Triangulation techniques were used to guarantee data quality and dependability, and descriptive qualitative analysis was used to examine the gathered data. According to the data, almost 73% of MSMEs in the Bantarjati souvenir center do not have full business licenses, which puts them at risk for fines, administrative penalties, and even business closure. From a business standpoint, unlicensed MSMEs face challenges in acquiring legal funding, restricted market access, and low competitiveness. Inadequate consumer protection is also a result of the lack of corporate legitimacy, which raises questions about legal responsibility, product quality assurance, and complaint procedures. The report emphasizes how urgently comprehensive policy initiatives are needed to increase MSME adherence to business licensing laws. To improve consumer protection, advance legal certainty, and guarantee the viability of MSMEs in the local economy, it is imperative to strengthen regulatory socialization, streamline licensing processes, and offer integrated assistance for MSMEs.